2022
DOI: 10.1200/go.21.00372
|View full text |Cite
|
Sign up to set email alerts
|

Building Capacity for Cancer Research in the Era of COVID-19: Implementation and Results From an International Virtual Clinical Research Training Program in Zambia

Abstract: PURPOSE The incidence of cancer in sub-Saharan Africa is increasing rapidly, yet cancer research in the region continues to lag. One contributing factor is limited exposure to clinical research among trainees. We describe implementation and results of a virtual clinical research training program for Zambian clinical oncology fellows developed jointly by the Cancer Diseases Hospital in Zambia and the MD Anderson Cancer Center to address this need. METHODS The clinical research training program consisted of 14 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“… 16 Additional endeavors such as virtual clinical research training programs have been implemented and developed jointly by cancer centers in Africa and the United Sates for clinical research training of clinical oncology fellows in the region. 17 Expansion of such virtual educational platforms in Asia can reduce the cost of training and enhance accessibility, and FARO is further working in this direction. Majority of the participants in the survey have expressed their interest toward participation in clinical research courses organized by the FARO research committee and have supported central coordination for conduct of research in the region.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Additional endeavors such as virtual clinical research training programs have been implemented and developed jointly by cancer centers in Africa and the United Sates for clinical research training of clinical oncology fellows in the region. 17 Expansion of such virtual educational platforms in Asia can reduce the cost of training and enhance accessibility, and FARO is further working in this direction. Majority of the participants in the survey have expressed their interest toward participation in clinical research courses organized by the FARO research committee and have supported central coordination for conduct of research in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Although these efforts have demonstrated the feasibility of virtual research mentoring, most remained institution specific. Meanwhile, we believe that virtual research mentoring may help break the bounds of nationality and facilitate participation in international research, an idea already shown to be plausible in a small, highly structured cancer research programme 11 . The relevance of virtual research mentoring was further reinforced by the COVID‐19 pandemic, which forced many in‐person learning activities, including research mentoring, to switch to virtual settings.…”
Section: Introductionmentioning
confidence: 86%
“…Whilst COVID-19 did not motivate the founding of our programme, we believe that COVID-19 has fundamentally changed medical education practices, with greater recognition of the potential and importance of virtual medical education. 11,12 Overall, we believe that our experience is ever more relevant to medical educators today, a belief that constituted the motivation for this article.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations